Efektivitas Pembelajaran Daring di Masa Pandemi Covid-19 - Aas Aliana Futriani Hidayah; Robiah Al Adawiyah; Prima Ayu Rizqi Mahanani (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2020)
Abstract— The Covid-19 pandemic that occurred in Indonesia made many changes in various sectors. The education sector is no exception, which is forced to change the learning system, which was originally face-to-face in schools, must be replaced with an online learning system. Even though technological developments have progressed, in reality the mastery of information and communication technology has not been mastered properly. Those who are involved in online learning also feel that they have not been able to implement it optimally. There are many obstacles and difficulties experienced by educators, students, and parents when implementing online learning. This study aims to determine the effectiveness of online learning during the Covid-19 pandemic in in Beji Hamlet, Sawiji Village, Jogoroto District, Jombang Regency. The result is that learning with online media is possible to be effective for students who are in areas where internet access is smooth, the facilities and infrastructure are supportive, and are not technologically illiterate. Keywords—: Effectiveness; Online Learning; Covid-19 Pandemic.